How is New England Coastal Sea Level Related to the Atlantic Meridional Overturning Circulation at 26° N?. Issue 10 (20th May 2019) - Piecuch, Christopher G.; Dangendorf, Sönke; Gawarkiewicz, Glen G.; Little, Christopher M.; Ponte, Rui M.; Yang, Jiayan
Abstract: Monthly observations are used to study the relationship between the Atlantic meridional overturning circulation (AMOC) at 26° N and sea level ( ζ ) on the New England coast (northeastern United States) over nonseasonal timescales during 2004–2017. Variability in ζ is anticorrelated with AMOC on intraseasonal and interannual timescales. This anticorrelation reflects the stronger underlying antiphase relationship between ageostrophic Ekman‐related AMOC transports due to local zonal winds across 26° N and ζ changes arising from local wind and pressure forcing along the coast. These distinct local atmospheric variations across 26° N and along coastal New England are temporally correlated with one another on account of large‐scale atmospheric teleconnection patterns. Geostrophic AMOC contributions from the Gulf Stream through the Florida Straits and upper‐mid‐ocean transport across the basin are together uncorrelated with ζ . This interpretation contrasts with past studies that understood ζ and AMOC as being in geostrophic balance with one another. Key Points: The AMOC at 26° N and New England coastal sea level are anticorrelated across intraseasonal and interannual timescales during 2004–2017 This anticorrelation reflects distinct local oceanic responses to temporally correlated, spatially disparate atmospheric forcing mechanisms The relevant local atmospheric forcing is related to the North Atlantic Oscillation, Arctic Oscillation, and West Atlantic Index